Recurrent Metastatic Basal Cell Carcinomas of the Face in a Patient with Gorlin–Goltz Syndrome - Petko Petrov; Dobromira Shopova; Georgi Goranov; Atanaska Dinkova; Nina Stoyanova; Nikolay Yanev (Current Oncology)
Gorlin–Goltz syndrome, also known as nevoid basal cell carcinoma syndrome (NBCCS), is a rare, inherited autosomal dominant disorder primarily caused by mutations in the PTCH1 gene, which regulates the Hedgehog signaling pathway. This genetic defect leads to the uncontrolled proliferation of basal cells, resulting in the formation of multiple basal cell carcinomas (BCCs) and odontogenic keratocysts (OKCs). This study aims to present a complex clinical case of a patient with Gorlin–Goltz syndrome who developed multiple recurrent metastatic basal cell carcinomas on the facial region, detailing the multidisciplinary treatment strategies employed and the challenges encountered during the management of the disease. The patient, diagnosed with a pathogenic PTCH1 gene mutation, underwent a series of treatment interventions over several years. These included multiple surgical excisions aimed at tumor removal, diverse radiotherapy approaches for residual or inoperable lesions, and systemic targeted therapy with Hedgehog pathway inhibitors to control tumor progression. The recurrent and aggressive nature of the basal cell carcinomas resulted in extensive facial tissue loss, posing significant challenges for radical tumor excision and subsequent reconstructive procedures. Multimodal therapeutic strategies, including Mohs micrographic surgery for precise tumor clearance and targeted systemic therapy with vismodegib, were implemented. However, the aggressive progression of lesions required ongoing surgical interventions, highlighting the limitations of current treatment modalities in achieving long-term disease control. This case underscores the critical need for a comprehensive, multidisciplinary approach to managing Gorlin–Goltz syndrome. Successful management requires close collaboration between dermatologists, oncologists, maxillofacial surgeons, and plastic surgeons to balance effective tumor control with optimal functional and aesthetic outcomes. The integration of advanced surgical techniques and targeted molecular therapies shows promise in improving patient outcomes. Nonetheless, early diagnosis, rigorous follow-up, and patient education remain essential components in minimizing disease progression and enhancing the quality of life for affected individuals.